Exploring marine microbial diversity: an overview of representative sampling strategies - Zrinka Ljubešić; Marija Gligora Udovič; Donata Overlingė; Filip Grgurević; Füsun Akgül; Ariola Bacu; Ana R. Díaz-Marrero; Dragana Drakulović; Stefano Fazi; Susana P. Gaudêncio; Anamarija Kolda; Lucie Novoveska; et al. (Frontiers in Marine Science, 2025)
The assessment of marine microbial biodiversity is crucial for determining either the environmental status (ecological or biodiversity research) or as a first step in the biodiscovery process (biotechnological research). Regardless of the research purpose, the first step in a biodiversity assessment is sampling, which can range from ad hoc sampling expeditions to long-term monitoring campaigns. In spite of its demands for funds, infrastructure, expertise, equipment, and personnel, sampling is often not adequately planned. This results in increased likelihood for biased sampling, which can lead to misinterpretation of results, omission of valuable specimens and an unrepresentative collection of stored samples, all particularly important for the assessment of microbial biodiversity. For these reasons, we are proposing a conceptual framework to assist in better preparation of sampling, consisting of pre-sampling, sampling and post sampling steps. The manuscript guides the reader through all the necessary steps, regardless of the sampling habitat (from water column to sediment), the sampling techniques and the preservation and storage approaches including culture and biorepositories. Such a harmonized approach can be of benefit for (i) researchers in the field of ecology/biotechnology, (ii) industrial companies requiring information on the providers and availability of data, and (iii) governance structures and funders, in the light of open science principles.

A walk in the PARC: developing and implementing 21st century chemical risk assessment in Europe - P. Marx-Stoelting; G. Rivière; M. Luijten; K. Aiello-Holden; N. Bandow; K. Baken; A. Cañas; A. Castano; S. Denys; C. Fillol; M. Herzler; I. Iavicoli; et al. (Archives of Toxicology, 2023)
Current approaches for the assessment of environmental and human health risks due to exposure to chemical substances have served their purpose reasonably well. Nevertheless, the systems in place for different uses of chemicals are faced with various challenges, ranging from a growing number of chemicals to changes in the types of chemicals and materials produced. This has triggered global awareness of the need for a paradigm shift, which in turn has led to the publication of new concepts for chemical risk assessment and explorations of how to translate these concepts into pragmatic approaches. As a result, next-generation risk assessment (NGRA) is generally seen as the way forward. However, incorporating new scientific insights and innovative approaches into hazard and exposure assessments in such a way that regulatory needs are adequately met has appeared to be challenging. The European Partnership for the Assessment of Risks from Chemicals (PARC) has been designed to address various challenges associated with innovating chemical risk assessment. Its overall goal is to consolidate and strengthen the European research and innovation capacity for chemical risk assessment to protect human health and the environment. With around 200 participating organisations from all over Europe, including three European agencies, and a total budget of over 400 million euro, PARC is one of the largest projects of its kind. It has a duration of seven years and is coordinated by ANSES, the French Agency for Food, Environmental and Occupational Health & Safety.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Valorization of Marine Waste: Use of Industrial By-Products and Beach Wrack Towards the Production of High Added-Value Products - Vita Rudovica; Ana Rotter; Susana P. Gaudêncio; Lucie Novoveská; Füsun Akgül; Linn Kristin Akslen-Hoel; Diogo A. M. Alexandrino; Olga Anne; Lauris Arbidans; Miroslava Atanassova; Magdalena Bełdowska; Jacek Bełdowski; et al. (Frontiers in Marine Science, 2021)
Biomass is defined as organic matter from living organisms represented in all kingdoms. It is recognized to be an excellent source of proteins, polysaccharides and lipids and, as such, embodies a tailored feedstock for new products and processes to apply in green industries. The industrial processes focused on the valorization of terrestrial biomass are well established, but marine sources still represent an untapped resource. Oceans and seas occupy over 70% of the Earth’s surface and are used intensively in worldwide economies through the fishery industry, as logistical routes, for mining ores and exploitation of fossil fuels, among others. All these activities produce waste. The other source of unused biomass derives from the beach wrack or washed-ashore organic material, especially in highly eutrophicated marine ecosystems. The development of high-added-value products from these side streams has been given priority in recent years due to the detection of a broad range of biopolymers, multiple nutrients and functional compounds that could find applications for human consumption or use in livestock/pet food, pharmaceutical and other industries. This review comprises a broad thematic approach in marine waste valorization, addressing the main achievements in marine biotechnology for advancing the circular economy, ranging from bioremediation applications for pollution treatment to energy and valorization for biomedical applications. It also includes a broad overview of the valorization of side streams in three selected case study areas: Norway, Scotland, and the Baltic Sea.

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

A New Network for the Advancement of Marine Biotechnology in Europe and Beyond - Ana Rotter; Ariola Bacu; Michèle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Meltem Conk Dalay; Thanos Dailianis; Irem Deniz; et al. (Frontiers in Marine Science, 2020)

A test of the evolution of increased competitive ability in two invaded regions - Michael C. Rotter; Mario Vallejo-Marin; Liza M. Holeski (Evolutionary Ecology, 2019)

Höchstmögliche räumlich-zeitliche Auflösung in der Lichtmikroskopie - Simon Dersch; Benjamin Mayer; Daniel A. O. Rotter; Luis M. Oviedo-Bocanegra; Peter L. Graumann (BIOspektrum, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

A meta-analysis of the evolution of increased competitive ability hypothesis: genetic-based trait variation and herbivory resistance trade-offs - Michael C. Rotter; Liza M. Holeski (Biological Invasions, 2018)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Genetic associations with lipoprotein subfraction measures differ by ethnicity in the multi-ethnic study of atherosclerosis (MESA) - Zhe Wang; Ani Manichukal; David C. Goff; Samia Mora; Jose M. Ordovas; Nicholas M. Pajewski; Wendy S. Post; Jerome I. Rotter; Michele M. Sale; Stephanie A. Santorico; David Siscovick; Michael Y. Tsai; et al. (Human Genetics, 2017)

Immortalised human mesenchymal stem cells undergo chondrogenic differentiation in alginate and PGA/PLLA scaffolds - K. Stölzel; G. Schulze-Tanzil; H. Olze; S. Schwarz; E. M. Feldmann; N. Rotter (Cell and Tissue Banking, 2015)

Erratum to: Empirical characteristics of family-based linkage to a complex trait: the ADIPOQ region and adiponectin levels - Jacklyn N. Hellwege; Nicholette D. Palmer; W. Mark Brown; Julie T. Ziegler; S. Sandy An; Xiuqing Guo; Y.-D. Ida Chen; Kent Taylor; Gregory A. Hawkins; Maggie C. Y. Ng; Elizabeth K. Speliotes; Carlos Lorenzo; et al. (Human Genetics, 2015)

Empirical characteristics of family-based linkage to a complex trait: the ADIPOQ region and adiponectin levels - Jacklyn N. Hellwege; Nicholette D. Palmer; Mark W. Brown; Julie T. Ziegler; Sandy S. An; Xiuqing Guo; Ida Y.-D. Chen; Kent Taylor; Gregory A. Hawkins; Maggie C. Y. Ng; Elizabeth K. Speliotes; Carlos Lorenzo; et al. (Human Genetics, 2015)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

Genetic variants associated with VLDL, LDL and HDL particle size differ with race/ethnicity - Alexis C. Frazier-Wood; Ani Manichaikul; Stella Aslibekyan; Ingrid B. Borecki; David C. Goff; Paul N. Hopkins; Chao-Qiang Lai; Jose M. Ordovas; Wendy S. Post; Stephen S. Rich; Michèle M. Sale; David Siscovick; et al. (Human Genetics, 2013)

Analysis of family- and population-based samples in cohort genome-wide association studies - Ani Manichaikul; Wei-Min Chen; Kayleen Williams; Quenna Wong; Michèle M. Sale; James S. Pankow; Michael Y. Tsai; Jerome I. Rotter; Stephen S. Rich; Josyf C. Mychaleckyj (Human Genetics, 2012)

In vitro activity of fosfomycin alone and in combination with amoxicillin, clarithromycin and metronidazole against Helicobacter pylori compared with combined clarithromycin and metronidazole - A. Blacky; A. Makristathis; P. Apfalter; B. Willinger; M. L. Rotter; A. M. Hirschl (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Novel human α1a-adrenoceptor single nucleotide polymorphisms alter receptor pharmacology and biological function - Beilei Lei; Daniel P. Morris; Michael P. Smith; Laura P. Svetkey; Mark F. Newman; Jerome I. Rotter; Thomas A. Buchanan; Stephen M. Beckstrom-Sternberg; Eric D. Green; Debra A. Schwinn (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

A Numerical Study of Micro-Heterogeneity Effects on Upscaled Properties of Two-Phase Flow in Porous Media - D. B. Das; S. M. Hassanizadeh; B. E. Rotter; B. Ataie-Ashtiani (Transport in Porous Media, 2004)

QTL for relative water content in field-grown barley and their stability across Mediterranean environments - B. Teulat; N. Zoumarou-Wallis; B. Rotter; M. Ben Salem; H. Bahri; D. This (Theoretical and Applied Genetics, 2003)

Risk Factors for Nasal Carriage of Staphylococcus aureus in Infectious Disease Patients, Including Patients Infected with HIV, and Molecular Typing of Colonizing Strains - D. Sissolak; A. Geusau; G. Heinze; W. Witte; M. Rotter (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Application of Blood-Based Polymerase Chain Reaction for Detection of Chlamydia pneumoniae in Acute Respiratory Tract Infections - P. Apfalter; J. Boman; M. Nehr; H. Hienerth; A. Makristathis; J. Pauer; F. Thalhammer; B. Willinger; M. Rotter; A. Hirschl (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Isolation and Continuous Growth of Chlamydia pneumoniae from Arterectomy Specimens - P. Apfalter; M. Loidl; R. Nadrchal; A. Makristathis; M. Rotter; M. Bergmann; P. Polterauer; A. M. Hirschl (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Helicobacter pylori Type I Strains Among Austrian and Portuguese Patients with Gastritis, Peptic Ulcer or Gastric Cancer - S. Bach; A. Makristathis; A. Pinto; M. Quina; M. Rotter; A. M. Hirschl (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Enteroaggregative and Enterotoxigenic Escherichia coli among Isolates from Patients with Diarrhea in Austria - E. Presterl; R. Nadrchal; D. Wolf; M. Rotter; A. M. Hirschl (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Molecular typing ofAcinetobacter baumannii from ten different intensive care units of a university hospital - E. Presterl; R. Nadrchal; S. Winkler; A. Makristathis; W. Koller; M. L. Rotter; A. M. Hirschl (European Journal of Clinical Microbiology & Infectious Diseases, 1997)